First evidence of transmission of an HIV-1 M/O intergroup recombinant virus. (2nd January 2016) - Ngoupo, Paul Alain; Sadeuh-Mba, Serge Alain; De Oliveira, Fabienne; Ngono, Valérie; Ngono, Laure; Tchendjou, Patrice; Penlap, Véronique; Mourez, Thomas; Njouom, Richard; Kfutwah, Anfumbom; Plantier, Jean-Christophe
Abstract : Objective: Despite the genetic divergence between HIV-1 groups M and O, HIV-1 M/O intergroup recombinants were reported. Actually, there is no data on the transmissibility of such recombinant forms. During a surveillance of HIV genetic diversity in Cameroon, we investigated the possible direct transmission of an HIV-1 M/O recombinant virus in an HIV-infected couple. Methods: Consecutive samples obtained from the couple were analysed for detection of dual HIV-1 groups M and O infections, and HIV-1 M/O recombinant forms. Analyses were performed using a serological and molecular algorithm based on HIV serotyping and group-specific PCRs targeting the polymerase and envelope genes. Pattern characterization of the strains found in both patients was based on complete genome sequencing. Phylogenetic and similarity profile analyses were performed to investigate the genetic relationship between viruses from both spouses and the previously described recombinant forms. Results: The sero-molecular algorithm data showed a group O serotype confirmed by molecular analysis in the envelope regions, whereas molecular tests identified HIV-1 group M in the polymerase. Phylogenetic analyses and similarity profiles of the full-length genome sequences showed that both spouses were infected with a unique recombinant virus having two recombination breakpoints in the vpr gene and LTR region. No phylogenetic link was found with the previous M/O recombinants. Conclusion: We provide, for the first time, molecular evidence of direct transmission of an HIV-1 M/O recombinant, highlighting the potential spread of these divergent viruses. The importance of HIV-1 recombination on genetic evolution and public health when implying divergent strains as group O has to be carefully considered. Abstract : Supplemental Digital Content is available in the text